THE ROLE OF LEADERSHIP SKILLS IN ENHANCING LANGUAGE TEACHING EFFECTIVENESS AMONG YOUTH - Risvayeva Charos Zaydilla qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Leadership skills play a crucial role in improving the effectiveness of language teaching among youth. In modern educational contexts, teachers are not only knowledge transmitters but also leaders who inspire, guide, and motivate learners. This article  explores  how  leadership  qualities  such  as  communication,  adaptability, emotional  intelligence,  and  decision-making  contribute  to  better  language  learning outcomes. By fostering a supportive and engaging classroom environment, educators with strong leadership skills can enhance student participation, confidence, and overall language proficiency. The study highlights the importance of integrating leadership development  into  teacher  training  programs  to  meet  the  evolving  needs  of  young learners in a globalized world.